Dissemination and Implementation Science for Oral Health: Why not consider de-implementation of low-value care to target oral health equity? - Bomfim, Rafael Aiello; Arriola-Pacheco, Fabio (Community Dental Health, 2025)
Dissemination and implementation sciences provide oral health professionals with an opportunity to understand which determinants promote the adoption of evidence-based innovations and interventions. Within this dynamic field, de-implementation provides the other side of the coin, that is, finding the ways to halt or modify practices that may be harmful to patients, do not hold sufficient scientific backing, or are simply not cost-efficient; conjointly known as low-value care. Scrutinizing low-value care procedures in oral health is essential, as identifying such practices creates opportunities to replace, update, or enhance them with approaches that offer greater benefits to patients, practitioners, and healthcare systems. Effective de-implementation begins with a clear understanding of which low-value practices persist. Only then can we conceptualize strategies to overcome barriers and promote more efficient, evidence-based care within the field. Furthermore, de-implementation can serve as a way to target oral health equity, as shifting away from low value care practices can lead to the better use of human and economic resources in those places where it is needed most. This commentary serves as a conceptualization of de-implementation within oral health, as well as, an invitation for the broader community to reflect on the importance of adequately mobilizing towards the delivery of more equitable care using the vigorous elements that dissemination and implementation science offer.